Hubungan Penggunaan Suara Harian dan Permasalahan Suara Pada Guru di Klaten - Miftahul Jannah; Hafidz Triantoro Aji Pratomo (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background: Education is a psychological discipline that specifically studies, researches and discusses all learning behavior, teaching behavior, and teaching-learning behavior by teachers and students who interact with each other. One form of voice disorders in the sound-forming organs is voice/speech fatigue. Teachers are significantly more likely than non-teachers to have voice disorders. this is by revealing the correlation of the load between the teacher's work when teaching with voice problems. Methods: This research is a quantitative research with a correlational descriptive research design. The sampling technique was carried out by Simple Random Sampling. The number of respondents to this study was 46 respondents. Thesis Results: The results of data analysis obtained a significant value of p = 0.628 (p > 0.05), which implies that the alternative hypothesis is rejected or there is no relationship between the two variables. Conclusion: There is no relationship between the duration of daily voice use in the teaching profession and voice problems in Klaten. This findings need to further exploration to find the voice use component in teachers. Keywords: Voice, Vocal Abuse, Teacher, Duration, Asssesment